Kimyo ta’limi samaradorligini oshirishning innovatsion texnologiyalari - Nizamova S.A, Abdurahimova G (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Attention to improving the quality of chemistry teaching in secondary schools in our country, problems and ways to solve them. Factors increasing the efficiency of chemical education, their types. Widespread use of innovative technologies. The main advantages and expected results of using innovative technologies in chemistry lessons.